STUDENTS’ RESPONSES TOWARD THE USE OF CONTEXTUAL TEACHING AND LEARNING - Yuni Arisanti; Yanuarti Apsari (PROJECT (Professional Journal of English Education), 2023)
In language learning, vocabulary plays a critical function. Learning to read, talk, write, and listen requires a strong vocabulary. People can't communicate or convey their feelings if they don't have a large vocabulary. These are the basic elements of English subjects. Vocabulary mastery is key for students to understand what they hear and read, and to communicate successfully with others. The purpose of this research is to identify students’ responses toward conyextual teaching and learning (CTL) in teaching vocabulary. This research used descriptive qualitative. The participants of this research are seventh grader of SMPN 2 Cipatat which consisted 30 students. This research used questionnaires as an instrument. The results of the analysis revealed that students responded positively to CTL. The respondents agree that CTL can help students improve vocabulary and made the students more active and interest in teaching learning process. Keywords:  Vocabulary; Contextual Teaching Learning (CTL); Students’ Responses